PENANAMAN ECO LITERASI MELALUI ENVIRONMENT PIONEER CLUB (EPIC) di SMPIT LHI - Siti Nofiati, S.Pd (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2023)
The phenomenon that is happening among the community today is the decline in public awareness of environmental cleanliness, one of which is the cleanliness of waste in the environment. The decline in concern for the cleanliness of waste makes the environment uncomfortable to live in and causes many viruses and infectious diseases. There needs to be an effort to increase public awareness of environmental cleanliness. One of the efforts made is through planting eco-literacy. Planting eco-literacy must be instilled from childhood through various activities. SMPIT LHI as an educational institution instills eco-literacy through a community called Environment Pioneer Club (EPIC). The purpose of this study is to provide knowledge and describe the EPIC (Environment Pioneer Club) program as an effort to cultivate ecoliteracy at SMPIT LHI. This research method uses descriptive qualitative methods with data collection techniques through observation, documentation and interviews. The results of the study show that Environment Pioneer Club (EPIC) has carried out various programs as an effort to inculcate ecoliteracy at SMPIT LHI including environmental care campaigns, waste sorting socialization, waste bank programs, and environmental sharing sessions. Various programs that have been implemented by Environment Pioneer Club (EPIC) have been able to have a positive impact on increasing the sense of awareness and concern for SMPIT LHI students.